Risk factors of under-five mortality in Tanzania: insights from the Tanzania Demographic and Health Survey 2022 - Md. Sazzad Hossan Sujon; Junayed Ahmmad; Imran Hossain Sumon; Md. Shahanewaj Asif; Mohammad Arifur Rahman; Tarequl Islam Manir; Deepmoy Ghosh; Umme Honey; Md. Moyazzem Hossain (BMJ Global Health, 2025)
Background Under-five mortality (U5M) is a key indicator and major concern of population health globally, which reflects the quality of maternal and childcare facilities and health services. Despite the significant decline globally, the challenge remains, especially in sub-Saharan Africa and South Asia, although Tanzania, a lower-middle-income country, is showing notable improvements, yet still needs attention to meet the Sustainable Development Goals (SDGs) by 2030. Therefore, this study aims to explore the socioeconomic, maternal, child and environmental risk factors of U5M in Tanzania.Methods This study is based on the secondary data extracted from the Tanzania Demographic and Health Survey 2022. The data consisting of 10 884 children were analysed through bivariate analysis, spatial analysis and a multilevel logistic regression model.Results It is observed that U5M was more prevalent in rural areas (adjusted OR (AOR): 1.878, 95% CI: 1.877 to 1.878). Findings also revealed that households that use improved drinking water (AOR: 0.921, 95% CI: 0.92 to 0.921) and are exposed to media (AOR: 0.945, 95% CI: 0.945 to 0.945) have lower odds for U5M. Multiple births (AOR: 5.518, 95% CI: 5.517 to 5.52) increased the odds of U5M, while postnatal care (AOR: 1.878, 95% CI: 1.877 to 1.878) and wealth index (poorer–AOR: 1.908, 95% CI: 1.908 to 1.909; middle–AOR: 1.533, 95% CI: 1.533 to 1.534; richer–AOR: 1.706, 95% CI: 1.705 to 1.706; richest–AOR: 2.950, 95% CI: 2.949 to 2.951) revealed counterintuitive results. It also revealed that minimum dietary diversity (AOR: 0.057, 95% CI: 0.057 to 0.057) reduces the chances of U5M, and the odds of mortality increase with child age.Conclusion The study highlights the spatial variability and risk factors of U5M in Tanzania. Therefore, it is necessary to address the identified determinants for reducing U5M in Tanzania to achieve the targeted interventions by policymakers and non-governmental organizations (NGOs) to improve child survival rates and meet the SDGs by 2030.